2019
DOI: 10.1007/s00371-019-01702-w
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between expert and beginner learning for motor skill development in a virtual reality serious game

Abstract: In order to be used for skill development and skill maintenance, virtual environments require accurate simulation of the physical phenomena involved in the process of the task being trained. The accuracy needs to be conveyed in a multimodal fashion with varying parameterisations still being quantified, and these are a function of task, prior knowledge, sensory efficacy and human perception. Virtual reality (VR) has been integrated from a didactic perspective in many serious games and shown to be effective in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
1
18
0
4
Order By: Relevance
“…Accordingly, it depends on the skill of the participant, his expertness, and his level of trainability to perceive the target, to focus, and predict its trajectory in the sky, then, to shoot it successfully. 2 Consequently, in shotgun sports practice, many variables can erratically change like the distance to the target which can become greater, the clay can move faster or slower through irregular trajectories (eg, launcher errors or irregular wind effect). Monfared, Tenenbaum 19 have stated that shooters with different levels of skill use visual feedback to detect performance errors and to anticipate outcomes.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, it depends on the skill of the participant, his expertness, and his level of trainability to perceive the target, to focus, and predict its trajectory in the sky, then, to shoot it successfully. 2 Consequently, in shotgun sports practice, many variables can erratically change like the distance to the target which can become greater, the clay can move faster or slower through irregular trajectories (eg, launcher errors or irregular wind effect). Monfared, Tenenbaum 19 have stated that shooters with different levels of skill use visual feedback to detect performance errors and to anticipate outcomes.…”
Section: Related Workmentioning
confidence: 99%
“…Clay pigeon sport shooting is a competition in which an athlete shoots a clay disc launched into the air. Accordingly, it depends on the skill of the participant, his expertness, and his level of trainability to perceive the target, to focus, and predict its trajectory in the sky, then, to shoot it successfully 2 . Consequently, in shotgun sports practice, many variables can erratically change like the distance to the target which can become greater, the clay can move faster or slower through irregular trajectories (eg, launcher errors or irregular wind effect).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although VR SGs can be entertaining, their fundamental purpose is to provide training and education to its users. VR-based serious games offer a secure space to conduct training that would be risky and costly in real life [9]. Studies have been conducted to show that the skills learned during a well-designed VR SGs are long-lasting [10] and depend mainly on the efficiency and wayfinding capabilities of participants [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although VR serious games can be entertaining, their primary purpose is to train or educate users. VR-based serious games offer a secure space to conduct training that would otherwise be risky and costly in real life [5,13]. Research has shown that the skills trained during VR serious games are strong and long-lasting [16].…”
mentioning
confidence: 99%